Extracellular biosynthesis of bimetallic Au-Ag alloy nanoparticles - Senapati, S.; Ahmad, Absar; Khan, Mohammad Islam; Sastry, M.; Kumar, R. (Small, 2005)
Keywords: alloys; Biosynthesis; composites; enzymes; Nanoparticles

Extra-/intracellular biosynthesis of gold nanoparticles by an alkalotolerant fungus, trichothecium sp. - Ahmad, Absar; Senapati, Satyajyoti; Khan, Mohammad Islam; Kumar, Rajiv; Sastry, Murali (Journal of Biomedical Nanotechnology, 2005)
The development of reliable, eco-friendly processes for the synthesis of nanoscale materials is an important aspect of nanotechnology. As part of our ongoing investigation into the use of fungi for nanoparticle synthesis, we report herein that depending on the reaction conditions of the fungus Trichothecium sp. with aqueous gold ions, gold nanoparticle synthesis can be controlled to occur either within the biomass or extracellularly. Moreover, we have found that reaction of gold ions with the Trichothecium sp. fungal biomass under stationary conditions results in the rapid extracellular formation of gold nanoparticles of spherical, rod-like and triangular morphology whereas reaction of the biomass under shaking conditions resulted in intracellular growth of the nanoparticles. It is believed that on changing the reaction conditions of the fungus with gold ions, the enzymes and proteins which are being released into the medium under stationary conditions do not get released under shaking conditions resulting in the formation of extracellular or intracellular gold nanoparticles respectively. The gold nanoparticles are not toxic to the cells and the cells continued to grow after the biosynthesis of the gold nanoparticles in both the cases.
Keywords: Biosynthesis; enzymes; Fungus; Gold; Morphology Control; Nanoparticles

Antagonism of microRNA function in zebrafish embryos by using locked nucleic acid enzymes (LNAzymes) - Suryawanshi, Hemant; Lalwani, Mukesh Kumar; Ramasamy, Soundhar; Rana, Rajiv; Scaria, Vinod; Sivasubbu, Sridhar; Maiti, Souvik (Chembiochem, 2012)
MicroRNAs (miRNAs) have crucial functions in many cellular processes, such as differentiation, proliferation and apoptosis; aberrant expression of miRNAs has been linked to human diseases, including cancer. Tools that allow specific and efficient knockdown of miRNAs would be of immense importance for exploring miRNA function. Zebrafish serves as an excellent vertebrate model system to understand the functions of miRNAs involved in a variety of biological processes. We designed and employed a strategy based on locked nucleic acid enzymes (LNAzymes) for in vivo knockdown of miRNA in zebrafish embryos. We demonstrate that LNAzyme can efficiently knockdown miRNAs with minimal toxicity to the zebrafish embryos.
Keywords: enzymes; locked nucleic acids; microRNA; morpholino; zebrafish

Extracellular biosynthesis of metal sulfide nanoparticles using the fungus fusarium oxysporum - Senapati, Satyajyoti; Syed, Asad; Khan, Shadab; Pasricha, Renu; Khan, Mohammad Islam; Kumar, Rajiv; Ahmad, Absar (Current Nanoscience, 2014)
The development of reliable, eco-friendly processes for the synthesis of nanomaterials is an important aspect of nanotechnology. One approach that shows immense potential is based on the biosynthesis of nanoparticles using microorganisms such as bacteria. In this report, we demonstrate the extracellular biosynthesis and complete characterization of metal sulfide (PbS, ZnS, MnS and NiS) nanoparticles using fungus, Fusarium oxysporum. We observed that the exposure of aqueous solution of 1 mM metal sulfate to fungus Fusarium oxysporum resulted in the formation of highly stable technologically important metal sulfide semiconductor nanoparticles. Fusarium oxysporum synthesizes lead sulfide and zinc sulfide nanoparticles of fractal type structure whereas manganese sulfide and nickel sulfide nanoparticles are of variable polydispersed morphology. The variable morphology may be due to the dissimilar interaction of metal sulfide nanoparticles with capping proteins secreted by the fungus in solution. The nanoparticles solution is found to be extremely stable with little evidence of aggregation even after a month of storage. The long term stability of the nanoparticles is due to the proteins secreted by fungus in the nanoparticle solution which bind to the surface of the nanoparticles and thus prevent aggregation.
Keywords: Biosynthesis; enzymes; fungi; metal sulfide; Nanoparticles

Biogenic green synthesis of monodispersed gum kondagogu (Cochlospermum gossypium) iron nanocomposite material and its application in germination and growth of mung bean (Vigna radiata) as a plant model - Raju, Dugyala; Mehta, Urmil J.; Beedu, Sashidhar Rao (IET Nanobiotechnology, 2016)
An eco-friendly green and one-pot synthesis of highly monodispersed iron (Fe) nanoparticles (NPs) by using a natural biopolymer, gum kondagogu (GK) as reducing and capping agent is proposed. The NPs synthesised were characterised by ultra-violet-visible spectroscopy, transmission electron microscopy, scanning electron microscopy and X-ray diffraction. As the concentration of gum and time increases, the intensity of NPs formation increased. The NPs were highly monodispersed with uniform circular shapes of 2-6 nm in size. The formed NPs were crystalline in nature which was confirmed by diffraction analysis. The conversion ratio of Fe ionic form to NPs was 21% which was quantified by inductively coupled plasma mass spectroscopy (ICP-MS). Fe is essential for plant growth and development. A study was conducted to examine the effect of these NPs on the growth of mung bean (Vigna radiata). The radical length and biomass was increased in seeds exposed to Fe NPs than the ions. The uptake of Fe NPs by the sprouts was also quantified by ICP-MS, in which Fe was more in mung bean seeds exposed to NPs. The -amylase activity was increased in the seeds exposed to NPs. The observed increase in the biomass by Fe NPs and seed germination may facilitate its application in the agriculture as an important cost-effective method for plant growth.
Keywords: alpha-amylase activity; Biogenic green synthesis; biological techniques; Biomass; Cochlospermum gossypium; diffraction analysis; enzymes; Fe; gum concentration; high-monodispersed iron nanoparticles; inductively coupled plasma mass spectroscopy; ionic-to-nanoparticle iron conversion ratio; iron; monodispersed gum kondagogu; monodispersed gum kondagogu iron nanocomposite material; mung bean germination; mung bean growth; Nanobiotechnology; Nanocomposites; nanoparticle formation; Nanoparticles; natural biopolymer; plant growth; plant model; scanning electron microscopy; size 2 nm to 6 nm; transmission electron microscopy; ultraviolet spectra; ultraviolet-visible spectroscopy; Vigna radiata; visible spectra; X-ray diffraction

Epoxy functionalized polymer grafted magnetic nanoparticles by facile surface initiated polymerization for immobilization studies of Candida Antarctica lipase B - Afzal, Haq Asif; Ghorpade, Ravindra V.; Thorve, Asmita K.; Nagaraja, Sreeharsha; Al-Dhubiab, Bandar E.; Meravanige, Girish; Rasool, Sahibzada Tasleem; Roopashree, Teeka S. (Reactive & Functional Polymers, 2020)
Immobilization of Candida Antarctica lipase B (Cal-B) was done on the epoxy functionalized polymer (EFP) grafted magnetic nanoparticles (MNPs) via covalent attachment with the active epoxy groups. The EFP brushes were grafted on iron-oxide based MNPs by a facile surface-initiated atom transfer radical polymerization (ATRP) using activators generated by electron transfer (AGET) of glycidyl methacrylate (GMA). Each step of the surface modification, polymer grafting, and enzyme immobilization process on the polymer grafted MNPs was studied using Fourier transform infrared spectroscopy (FTIR). A thermogravimetric analysis (TGA) calculated the amount of engineered organic components, a transmission electron microscopy (TEM) visualized the core-shell formation of the MNPs, and a vibrating sample magnetometer (VSM) validated their magnetic properties at various modification stages. The lipase immobilization efficiency was described as a function of immobilization time, as well as, enzyme amount. The activity was characterized within a range of pH, temperature, kinetic parameters, resusability and storage stability, for both the free and immoblized Cal-B enzyme. The results of this study suggested that poly(GMA) grafted MNPs can be successfully used for the immobilization of Cal-B with improved efficiencies compared to those obtained with free soluble lipase. The reported enzyme immobilization method appears to be reproducible and scalable for industrial production.
Keywords: Cal-B enzymes; enzymes; Immoblization; Magnetic nanoparticles

Synthesis of phospho-polypeptides via phosphate-containing N-carboxyanhydride: application in enzyme-induced self-assembly, and calcium carbonate mineralization - Mondal, Basudeb; Das, Soumen; Panda, Sidharth; Dutta, Tahiti; Sen Gupta, Sayam (ChemPlusChem, 2020)
An easy synthetic strategy was developed to synthesize the phosphate-functionalized amino acid N-carboxyanhydride (NCA), using simple primary amine initiators to obtain homo and block phospho-polypeptides with controlled molecular weight and molecular weight distribution. The methodology was extended to the synthesis of the end-functionalized homo polypeptides (15 to 50 repeat unit) and block co-polypeptides with PEG (0.7 K, 2 K, and 5 K) and glycopolypeptide (15-unit mannose glycopolypeptide) as one of the blocks. The deprotected fully water-soluble anionic phosphate-based polypeptides showed pH-dependent helical conformation with a helical content of 20 %, which further changed to beta-sheets upon addition of the enzyme alkaline phosphatase (ALP) due to dephosphorylation. The block co-polypeptide containing PEG as one of the blocks led to its self-assembly into colloidal structures, such as vesicles with a hydrodynamic diameter of similar to 250 nm, due to the formation of amphiphilic block co-polymer upon dephosphorylation. The nature of the colloidal structures formed can be temporally controlled by the extent of dephosphorylation. Finally, the phospho-polypeptides serve as a template for the mineralization of calcium carbonate with varying polymorphs and morphologies.
Keywords: Biomineralization; enzymes; phosphopolypeptides; Proteins; Self-assembly